Social Customer Relationship Management, an emerging strategy for customer loyalty - Dominguez-Espiritu, Reveca N. (2025)
In the digital age, the key to business success lies in effective customer relationship management. Social Customer Relationship Management (SCRM) is emerging as a disruptive strategy by integrating the dynamics of social media into customer relationship management (CRM). This study seeks to determine the extent to which the Social Customer Relationship Management (SCRM) strategy relates to customer loyalty. It presents a quantitative, basic approach, correlational level, and non-experimental design. The population comprises 446 customers, of which 207 constitute the sample. The results obtained from the Spearman's Rho statistical test yielded a p value of 0.000 < 0.05 and a coefficient of 0.789, supporting the existence of a very strong and significant positive relationship between SCRM implementation and customer loyalty. This finding highlights the importance of the SCRM strategy in directly improving customer perceptions of the services offered, thus consolidating the company's competitive position in the market and contributing to long-term customer loyalty.